Anti-human-TIGIT agonistic antibody ameliorates autoimmune diseases by inhibiting Tfh and Tph cells and enhancing Treg cells - Kojima, Marenori; Suzuki, Katsuya; Takeshita, Masaru; Ohyagi, Masaki; Iizuka, Mana; Yamane, Humitsugu; Koga, Keiko; Kouro, Taku; Kassai, Yoshiaki; Yoshihara, Tomoki; Adachi, Ryutaro; Hashikami, Kentarou; et al. (Communications biology, 2023)
T cells play important roles in autoimmune diseases, but it remains unclear how to optimally manipulate them. We focused on the T cell immunoreceptor with Ig and ITIM domains (TIGIT), a coinhibitory molecule that regulates and is expressed in T cells. In autoimmune diseases, the association between TIGIT-expressing cells and pathogenesis and the function of human-TIGIT (hu-TIGIT) signalling modification have not been fully elucidated. Here we generated anti-hu-TIGIT agonistic monoclonal antibodies (mAbs) and generated hu- TIGIT knock-in mice to accurately evaluate the efficacy of mAb function. Our mAb suppressed the activation of CD4 + T cells, especially follicular helper T and peripheral helper T cells that highly expressed TIGIT, and enhanced the suppressive function of naïve regulatory T cells. These results indicate that our mAb has advantages in restoring the imbalance of T cells that are activated in autoimmune diseases and suggest potential clinical applications for anti-hu-TIGIT agonistic mAbs as therapeutic agents. A monoclonal human T cell immunoreceptor with Ig and ITIM domains (TIGIT) agonistic antibody in a TIGIT knock-in mouse model suppresses follicular and peripheral helper T cell activation and enhances suppression effects of naive regulatory T cells.